Thermodynamic phase diagrams, thermoelectric, and half-metallic properties of KCaX2(X=N, O) and their [001] films - Nezhad, Kobra Ghafouri; Boochani, Arash; Nia, Borhan Arghavani; Rezaee, Sahar (Indian journal of physics, 2023)
Applying density functional theory (DFT) calculations, a report on the electronic structure of two full-Heusler combinations KCaX 2 (X=N, O) and their [001] films is presented. Examination of elastic parameters and phase diagrams provided that KCaN 2 and KCaO 2 bulk structures as well as their four possible terminations, N–N, O–O, K–Ca:KCaN2, and K–Ca:KCaO2, can be synthesized in laboratory. These two Heusler bulk structures, as well as their N–N and O–O terminations, are ferromagnetic half-metals with 100% spin polarization at the Fermi level. The presence of flat valence bands in the Γ - X direction for KCaN 2 , KCaO 2 , and two terminations of N–N and O–O indicates the high effective mass of the holes in these materials, and it promises an excellent thermoelectric behavior of these compounds. The dimensionless figure of merit index (ZT) obtained for these materials is large and good numbers, indicating that the formation of film [001] has led to an improvement in the performance of these Heusler compounds.